2020
DOI: 10.1021/acsami.0c09374
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Enhancing Solar Scattering for Direct Radiative Cooling through Control of Polymer Nanofiber Morphology

Abstract: Radiative cooling can alleviate urban heat island effects and passively improve personal thermal comfort. Among many emerging approaches, infrared (IR) transparent films and fabrics are promising because they can allow objects to directly radiate heat through bands of atmospheric transparency while blocking solar heating. However, achieving high solar reflectance while maintaining IR transmittance using scalable nanostructured materials requires control over the shape and size distribution of the nanoscale bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Much work has been done for mid-infrared (MIR)-transparent radiative cooling textiles. [70][71][72] And a small thickness of < ~150 μm is usually needed to maintain enough MIR transmittance, limiting the solar reflectivity (discussed in the following section) and mechanical strength. On the other hand, the performance of MIR-emissive textiles does not depend on the spectrum of the underlying surface and thus relaxes restrictions on thicknesses.…”
Section: Improved Thermal Mid-infrared Emittancementioning
confidence: 99%
“…Much work has been done for mid-infrared (MIR)-transparent radiative cooling textiles. [70][71][72] And a small thickness of < ~150 μm is usually needed to maintain enough MIR transmittance, limiting the solar reflectivity (discussed in the following section) and mechanical strength. On the other hand, the performance of MIR-emissive textiles does not depend on the spectrum of the underlying surface and thus relaxes restrictions on thicknesses.…”
Section: Improved Thermal Mid-infrared Emittancementioning
confidence: 99%
“…In one study, polyacrylonitrile nanofibers were electrospun and fiber morphology was varied to control optical properties. 44 Fiber diameter varied between 0.2 and 1 μm as the fiber morphology varied from beaded to cylindrical. Large changes in solar reflectance and LWIR transmission were observed among the different nanofiber mats.…”
Section: Selective Transmitters-reflectors For Coolingmentioning
confidence: 99%
“…Recently, anisotropic fibrous media that are similar to ours have been studied for radiative cooling applications. [ 25–27 ] Li et al [ 25 ] used electrospun polyethylene oxide to have a mid‐IR emissivity spectrum desired for radiative cooling. For maximum solar rejection, they determined that a fiber diameter should be in the range of 0.5–1.2 μm, comparable to solar wavelengths, based on scattering efficiency calculations (the optimum diameter would have been 0.746 μm, see Section 10, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The numerical study showed that a fiber diameter of 0.4–0.5 μm at a fiber fraction of 0.04 yielded the maximum radiative cooling under sunlight when the film thickness was below 1 mm. Kim et al [ 27 ] used electrospun polyacrylonitrile to render low solar transmissivity and high mid‐IR transmissivity. Ellipsoidal beadings on the fibers of a 0.067 μm in diameter increased solar reflectivity.…”
Section: Introductionmentioning
confidence: 99%